Preservice Teachers’ Readiness in Utilizing Innovative Educational Technology at UIN K.H. Abdurrahman Wahid Pekalongan - Nur Afifah; Inas Farrah Dina Noor; Fina Fatkhurizqia (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
The integration of innovative educational technology has become an urgent demand in 21st-century education. Preservice teachers, as future educators, are expected to master not only pedagogical and subject knowledge but also the creative use of technology to enhance teaching and learning. This study aims to analyze the readiness of preservice teachers at UIN K.H. Abdurrahman Wahid Pekalongan in utilizing innovative educational technology. Employing a descriptive qualitative approach, the study involved five students of the Faculty of Tarbiyah and Teacher Training, selected purposively. Data were collected through a Google Form questionnaire exploring understanding, experience, readiness, challenges, and expectations regarding the use of innovative educational technology. The findings reveal that preservice teachers’ understanding of technology varies significantly, ranging from high competence to limited awareness. Experiences in using digital learning platforms such as Google Classroom, Kahoot, and Quizizz also differ, creating a gap in confidence levels. Despite technical limitations, most students demonstrate positive attitudes and strong motivation to integrate technology into their future teaching. However, challenges such as limited access to devices, lack of intensive training, and insufficient institutional support remain obstacles. Students hope for more workshops, courses, and direct practice opportunities provided by the university. In conclusion, preservice teachers show strong potential but require systematic institutional support to fully adapt to the demands of innovative education.